2016
DOI: 10.1377/hlthaff.2015.0919
|View full text |Cite
|
Sign up to set email alerts
|

Hospitals Participating In ACOs Tend To Be Large And Urban, Allowing Access To Capital And Data

Abstract: Relationships between physicians and hospitals have changed considerably over the past decade as hospitals and physician groups integrate and new public and private payment policies create financial interdependence. The extent to which accountable care organizations (ACOs) involve hospitals in their operations may prove to be vitally important because managing hospital care is a key part of improving quality and lowering cost growth. Using primary data on ACO composition and capabilities paired with hospital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
87
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 21 publications
(24 reference statements)
9
87
2
Order By: Relevance
“…Moreover, compared with hospital-integrated ACOs, ACOs that are independent physician groups report similar capacity for influencing inpatient care—and thus decisions about post-acute care at discharge—presumably by staffing admissions directly or using hospitalist groups or care managers to influence their patients’ inpatient care. 10 Our results are consistent with ACOs using similar strategies to shorten length of SNF stays, such as employing or partnering with clinicians to follow patients in SNFs.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, compared with hospital-integrated ACOs, ACOs that are independent physician groups report similar capacity for influencing inpatient care—and thus decisions about post-acute care at discharge—presumably by staffing admissions directly or using hospitalist groups or care managers to influence their patients’ inpatient care. 10 Our results are consistent with ACOs using similar strategies to shorten length of SNF stays, such as employing or partnering with clinicians to follow patients in SNFs.…”
Section: Discussionsupporting
confidence: 85%
“…11 Recent studies have shown that commercial and noncommercial ACOs are increasing in number; half are led by physician groups; and included hospitals are more likely to be nonprofit, mid-size and large hospitals in the Northeast and Midwest. 10,1214 …”
mentioning
confidence: 99%
“…[3,22] Organizations owning hospitals and specialty practices have weaker incentives than those that do not to limit use of inpatient and specialty care under ACO contracts, and evidence from Medicare and commercial ACO initiatives suggests that providers can successfully influence use of care in multiple settings without formal ownership arrangements uniting providers. [3,23,24]…”
Section: Empirical Evidence and The Prevailing Concernmentioning
confidence: 99%